2018
DOI: 10.1093/eurheartj/suy019
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Document ANMCO/ANCE/ARCA/GICR-IACPR/GISE/SICOA: Long-term Antiplatelet Therapy in Patients with Coronary Artery Disease

Abstract: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor inhibitor is the cornerstone of pharmacologic management of patients with acute coronary syndrome (ACS) and/or those receiving coronary stents. Long-term (>1 year) DAPT may further reduce the risk of stent thrombosis after a percutaneous coronary intervention (PCI) and may decrease the occurrence of non-stent-related ischaemic events in patients with ACS. Nevertheless, compared with aspirin alone, extended use of aspirin plus a P2Y12 receptor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 380 publications
0
15
0
1
Order By: Relevance
“…As is the case with percutaneous coronary intervention, the use of anticoagulants (warfarin sodium) or dual antiplatelet therapy (aspirin and clopidogrel) should be considered to prevent early stent occlusion. 11 However, those therapies were not initiated in our case because of risk of rebleeding during further endoscopic procedure. Therefore, aspirin alone was used as antiplatelet therapy in our case.…”
Section: Discussionmentioning
confidence: 90%
“…As is the case with percutaneous coronary intervention, the use of anticoagulants (warfarin sodium) or dual antiplatelet therapy (aspirin and clopidogrel) should be considered to prevent early stent occlusion. 11 However, those therapies were not initiated in our case because of risk of rebleeding during further endoscopic procedure. Therefore, aspirin alone was used as antiplatelet therapy in our case.…”
Section: Discussionmentioning
confidence: 90%
“…The major limitation of the study is that patients put on 325 mg/day aspirin for 2 days and then switched to 100 mg aspirin q.d. The dose of 100 mg/day spirin is a low dose to observe angiotensin-converting enzyme inhibitor–aspirin interaction, 5 but the safest dose for long-term use is ⩽100 mg. 15 , 16 In addition, this was a retrospective study, and there was no control group. The study was performed for just 1 year, while the results of the SMILE study were evaluated after 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ADP is the P2Y12 receptor agonist, while adenosine triphosphate (ATP) is the receptor antagonist that increases the production of cAMP and therefore reduces platelet aggregation. (Gulizia et al 2018) Clopidogrel has been widely studied and shown to reduce cardiovascular events among patients with atherosclerotic disease. Among high-risk patients with ischemic stroke, MI, or established PAD, clopidogrel monotherapy was associated with a 7.9% relative risk reduction in MI, ischemic stroke, vascular death, or rehospitalization compared with aspirin.…”
Section: Clopidogrelmentioning
confidence: 99%